Pendidikan Holistik Berbasis Keagamaan Pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama Islam Terpadu Bina Ummah - Iffan Ahmad Gufron; Nani Rosini; Taufiqurrahman Taufiqurrahman (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2020)
Schools always innovate in carrying out programs that are carried out through daily religious activities at school so that students do not feel bored and bored in the learning process or activities in the school. These religious activities are packaged in Islamic Religious Education (PAI) lessons. however it is still ignored by students. The purpose of this paper is to describe the strategy of delivering religion in Islamic Education subjects, developing the potential of students, and the importance of holistic education. This research uses a qualitative approach with a case study design. Data were collected by in-depth interviews, observation and documentation. Data analysis used interactive analysis through data reduction, data display, verification and conclusion stages. Furthermore, the results of the research show that holistic religious-based education in Islamic Education which is applied at SMP IT BINA UMMAH SUMBER includes 1) Implementation of religious-based holistic education in Islamic Education lessons; and 2) to determine the factors inhibiting and encouraging religious-based holistic education in Islamic Education lessons. It can be concluded that holistic religion-based education is education that develops all the potential that exists in students. The results of this study are expected to develop all the potential to be realized as character building in students. Abstrak Sekolah selalu berinovasi dalam melakukan program-program yang dijalankan melaui kegiatan keagamaan pada keseharian di sekolah sehingga peserta didik tidak merasa bosan dan jenuh dalam proses belajar maupun kegiatan yang ada di sekolah kegiatan keagamaan tersebut dikemas pada pelajaran Pendidikan Agama Islam (PAI) akan tetapi masih diabaikan pada peserta didik. Tujuan penulisan ini adalah untuk mendeskripsikan strategi penyampaian keagamaan pada mata pelajaran PAI, pengembangan potensi peserta didik, dan Urgensi pendidikan holistik. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan dengan wawancara mendalam, observasi dan dokumentasi. Analisis data menggunakan analisis interaktif melalui tahap reduksi data, display data, verifikasi dan kesimpulan. Selanjutnya, hasil dari penelitian menujukkan bahwa pendidikan holistik berbasis keagamaan pada pelajaran PAI yang diterapkan di SMP IT BINA UMMAH SUMBER meliputi 1) Implementasi pendidikan holistik berbasis keagamaan pada pelajaran PAI; dan 2) untuk mengetahui faktor-faktor penghambat dan pendorong pendidikan holistik berbasis keagamaan pada pelajaran PAI. Dapat disimpulkan bahwa pendidikan holistik berbasis keagamaan adalah pendidikan yang mengembangkan seluruh potensi yang ada pada peserta didik. Hasil penelitian ini diharapkan dalam mengembangkan seluruh potensi diwujudkan sebagai pembentukan karakter pada peserta didik.